Facial reconstruction as a means of identification in legal dentistry: literature review (Research, Society and Development, 2022)
Objective: to know the role of legal dentistry for human identification, through forensic facial reconstruction, as well as the different techniques used and the main dental resources used in this process. Methodology: A narrative review of the literature was carried out. The descriptors forensic dentistry, facial reconstruction and forensic anthropology were used. Literature review: The application of human identification methods is a necessity in the context of the work of Medico-Legal Institutes. The forensic work to determine the identity of a corpse is a challenge, especially when it is partially destroyed, as in the cases of dismembered, disfigured, skeletonized, charred bodies, victims of mass disaster, putrefied, among others. Final considerations: Forensic Dentistry has a significant role in the identification method, making it safe and of fundamental importance, since identification is a resource that needs to be introduced in the Forensic and Dental Expertise scenario, contributing to justice effectively for effective identification.